Numerical simulations to study nonlinear wave-based interaction and turbulent magnetic field amplification in the laboratory and astrophysical plasmas. (1st September 2022) - Dewan, Himani; Singh, Indraj; Uma, R; Sharma, R P
Abstract: A theoretical model is proposed to study the interaction of high-frequency oblique whistler wave (OWW) and low-frequency kinetic Alfvén waves (KAWs). In our previous investigation (Dewan et al 2020 Phys. Plasmas 27 032111), we established the existence of these two plasma modes (OWW and KAW) by virtue of parametric decay instability. For the present investigation, a numerical simulation technique is employed to solve the coupled system of equations. The ponderomotive force exerted by OWW excites the low-frequency KAW. This quasi-static force induces the genesis of density cavitation (regions of accumulation and depletion) in low-frequency KAW in the magnetized plasma. The simulation results give the localization of the OWW, which amplifies with time. At a later time, the structures become chaotic. The energy cascade is presented in terms of the ensemble-averaged power spectrum. We have also developed a semi-analytical model for this wave–wave interaction mechanism to understand the underlying physics of the field localization process.